Change in the Prevalence of Testing for Latent Tuberculosis Infection in the United States: 1999–2012 - Nicholas T. Vozoris; Jane Batt (Canadian Respiratory Journal)
Purpose. There is no information on the change in prevalence of latent tuberculosis infection (LTBI) testing in the United States (US) following the introduction of the interferon gamma release assay (IGRA), a new and alternative diagnostic method for LTBI. The purpose of this study was to evaluate potential changes in the prevalence of LTBI testing in the US following the introduction of IGRA. Methods. This was a multiyear cross-sectional study using nationally representative data from the 1999-2000 and 2011-2012 US National Health and Nutrition Examination Surveys. Self-reported prevalence of LTBI testing was estimated among groups known to have increased LTBI risk. Descriptive statistics were used. Results. Compared to 1999-2000, significantly fewer individuals self-reported being tested for LTBI in 2011-2012 among Hispanic Americans (68.0% versus 60.7%, p<0.0001) and among those with comorbidities (74.7% versus 72.0%, p=0.02). There were also nonsignificant trends towards less self-reported LTBI testing in 2011-2012 versus 1999-2000 among household contacts of active TB cases, foreign-born individuals, and African Americans. Conclusions. Despite the introduction of IGRA, LTBI testing occurs less frequently in the US among vulnerable groups. Possibly inadequate targeted LTBI testing could result in increased active TB in the US in the future.